(untitled) (Jurnal Ekonomi dan Kebijakan Pembangunan, 2023)
The increasing use of private digital currency can affect the effectiveness of the monetary policy, putting the government under pressure to adopt the Central Bank Digital Currency (CBDC). This study aims to analyze the factors that influence economic actors in the use of CBDC. The results showed that the effectiveness and safety may increase the consumer satisfaction with using CBDC and the publicity influences changes in the behavior of economic actors in increasing the conversion of fiat money to CBDC.